2018
DOI: 10.1021/acsaem.7b00207
|View full text |Cite
|
Sign up to set email alerts
|

Whispering Gallery Mode Assisted Enhancement in the Power Conversion Efficiency of DSSC and QDSSC Devices Using TiO2 Microsphere Photoanodes

Abstract: Mesoporous TiO2 nanoparticles are excellent photoanodes for sensitized solar cells (SSC). However, a significant loss in the photoconversion efficiency (PCE) occurs due to the inefficient light absorption. Large Mie scattering from mesoporous micron-sized spheres could be used to enhance the absorption and hence the PCE. Here, we show that a composite comprising a TiO2 mesoporous microsphere with smooth surface (SμS-TiO2) exhibiting whispering gallery modes (WGM) and a commercial TiO2 mesoporous nanoparticle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…Later, it was shown that a significant increase in efficiency, in fact, arises from the increased absorption by the dye, mainly modulated by the WGM arising from the microspheres (Das et al, 2018a). Similar enhancement was shown to prevail in QDSSC and semiconductor sensitized solar cell (SCSSC) devices (Das et al, 2018a;Ilaiyaraja et al, 2019). Extensive studies carried out by fabricating QDSSC devices using CdSe QDs and CuInS 2 QDs are reported (Das et al, 2018a;Ilaiyaraja et al, 2018).…”
Section: Wgm To Boost the Efficiency In Dsscs/qdsscsmentioning
confidence: 93%
See 4 more Smart Citations
“…Later, it was shown that a significant increase in efficiency, in fact, arises from the increased absorption by the dye, mainly modulated by the WGM arising from the microspheres (Das et al, 2018a). Similar enhancement was shown to prevail in QDSSC and semiconductor sensitized solar cell (SCSSC) devices (Das et al, 2018a;Ilaiyaraja et al, 2019). Extensive studies carried out by fabricating QDSSC devices using CdSe QDs and CuInS 2 QDs are reported (Das et al, 2018a;Ilaiyaraja et al, 2018).…”
Section: Wgm To Boost the Efficiency In Dsscs/qdsscsmentioning
confidence: 93%
“…The composite structure proposed by Ilaiyaraja et al possesses properties of high light scattering, higher surface area, and low interfacial resistance, which are desired for efficient electron generation and transport (Ilaiyaraja et al, 2017). Later, it was shown that a significant increase in efficiency, in fact, arises from the increased absorption by the dye, mainly modulated by the WGM arising from the microspheres (Das et al, 2018a). Similar enhancement was shown to prevail in QDSSC and semiconductor sensitized solar cell (SCSSC) devices (Das et al, 2018a;Ilaiyaraja et al, 2019).…”
Section: Wgm To Boost the Efficiency In Dsscs/qdsscsmentioning
confidence: 97%
See 3 more Smart Citations